ChemInform Abstract: Identification of Six New Minor Diarylheptanoids from the Seeds of Alpinia katsumadai. Issue 9 (4th March 2014) - Nam, Joo‐Won; Seo, Eun‐Kyoung
Abstract isolation and structure elucidation of katsumains D—G (I)—(III) and two new alpinikatin derivatives (IV)